Alteration in Uterine Protease-Activated Receptor 2 Expression in Preterm Birth Induced Experimentally in Brp-39 Null Mutant Mice. (June 2019) - Jang, Ja Yun; Kim, Yi Seul; Han, Yu Mi; Kang, So Young; Kim, Jung-Sun
Breast regression protein 39 (Brp-39) is a mouse homolog of human Chitinase 3-like 1, which belongs to the 18-glycosyl-hydrolase family and plays a role in inflammatory reaction and tissue remodeling. The aim of this study is to investigate the role of Brp-39 in a mouse model of preterm birth. Pregnant wild-type (WT) or Brp-39 (−/−) mice were injected intraperitoneally with lipopolysaccharide (LPS) at embryonic day 15. Pregnancy outcomes were evaluated for 24 hours after LPS injection. Quantitative real-time polymerase chain reaction and immunoblotting were performed to analyze messenger RNA (mRNA) and protein expressions of cytokines and contraction-associated proteins in uterine and/or placental tissue after LPS injection. LPS injection led to preterm birth in both WT and Brp-39 (−/−) mice, but the proportion of pubs delivered was reduced in Brp-39 (−/−) mice, along with a longer interval from the LPS injection to delivery, compared to WT mice. Inflammatory cell infiltration and mRNA expression of cytokines and Ptgs2 in the uteri and the placentas were not significantly different between WT and Brp-39 (−/−) mice. Par-2 mRNA expression in the WT uteri was increased before delivery after LPS injection and decreased after delivery, while there was no significant change in Par-2 expression in the Brp-39 (−/−) uteri. Protein expressions of Par-2 and Ptgs2 were lower in the Brp-39 (−/−) uteri than in the WT uteri before and after delivery. Attenuated preterm birth in Brp-39 (−/−) mice indicates the significance of Brp-39 during murine preterm birth. Altered expression of Par-2 in Brp-39 (−/−) uteri suggests its potential role in attenuated preterm birth of Brp-39 (−/−) mice.